Sistem Informasi Pelaporan Status Gizi Balita Berbasis Web di Puskesmas Banjarsengon - Firdaus Sholehah (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2019)
Recording and reporting nutritional status at the Banjarsengon Community Health Center is still manual and uses Excel. The report also includes the process of determining or calculating the nutritional status of children under five. The use of Excel has many limitations such as the absence of a password for toddlers data security, the process of rearranging the Excel sheet for printing and so on. The purpose of this study was to design and create a web-based nutritional status reporting information system for children under five in the Banjarsengon Health Center using the waterfall method. Data collection is done by interview, observation, and documentation. The results of this study are web-based nutritional status reporting information systems with several advantages, in addition to focusing on calculating the nutritional status of children under five, this information system can also make detailed nutritional status reports for toddlers. The detailed report in question is a toddler report which is grouped based on nutritional problems experienced by toddlers and their solutions. This information system is expected to make it easier for nutrition workers at the Banjarsengon Health Center to carry out their duties.